2008 3rd IEEE Symposium on New Frontiers in Dynamic Spectrum Access Networks 2008
DOI: 10.1109/dyspan.2008.22
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Selfish Behavior in a Cooperative Commons

Abstract: A cooperative commons is a type of ad hoc network in which all devices are required to communicate and carry each other's traffic, even when devices are associated with different administrative domains. Thus, infrastructure is constructed at little cost to each owner. One unusual feature of the cooperative commons is that as more devices join, total communication capacity increases. These advantages are possible when devices are willing to cooperate and use their own resources to carry traffic of others, but a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…As with the cooperative commons discussed in Section III-A, the problem is compounded by the fact that devices may be amply rewarded for providing misinformation to neighbors [26], perhaps convincing those neighbors to switch to another band by falsely claiming that the primary system is active. If it is necessary that all devices must follow the same cooperative algorithms, then someone must define those algorithms, enforce them on all secondary devices deployed in the band, and handle violations.…”
Section: Sharing Among Equal Secondaries Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…As with the cooperative commons discussed in Section III-A, the problem is compounded by the fact that devices may be amply rewarded for providing misinformation to neighbors [26], perhaps convincing those neighbors to switch to another band by falsely claiming that the primary system is active. If it is necessary that all devices must follow the same cooperative algorithms, then someone must define those algorithms, enforce them on all secondary devices deployed in the band, and handle violations.…”
Section: Sharing Among Equal Secondaries Devicesmentioning
confidence: 99%
“…When devices delay their own transmissions for another, or carry each other's traffic, some altruism is required, e.g., one device might increase delays for its own traffic and drain its own battery by transmitting a stranger's packet. For example, we have shown that devices can manipulate today's routing protocols to avoid carrying traffic for other devices, thereby improving their own performance, and it is only possible to detect such behavior with nonstandard protocol modifications [26]. Even worse, a malicious node may take deliberate steps to disrupt the network, and in some proposed cooperative schemes, the impact of malicious behavior could be great.…”
Section: A Sharing Among Equal Primary Devicesmentioning
confidence: 99%
“…In the RREP header, in addition to these two, another field called next_to_destination is added to indicate the node to which the packet is to be forwarded in the reverse path. With these additional fields, it is possible to detect every instance of selfish behavior in a wireless network, if the following conditions are satisfied: (i) no packet is lost due to interference, (ii) links are bi-directional, (iii) the nodes are stationary, and (iv) queuing delays are bounded [13]. The robust clustering and monitoring with additional fields substantially increase the detection as evident from the results.…”
Section: The Detection Algorithmmentioning
confidence: 92%
“…In the header of an RREQ packet, in addition to the above two fields, another field called next_to_destination is added to indicate the address of the node to which the packet must be forwarded in the reverse path. It has been shown in (Kim et al, 2008), with the above extra fields, it is possible to detect every instance of selfish behavior in a wireless network with 100% detection accuracy, if the following conditions are satisfied: (i) no packet loss lost due to interference, (ii) links are bi-directional, (iii) the nodes are stationary, and (iv) the queuing delays are bounded. Since all these conditions cannot be guaranteed in a realworld deployment, there will be always some detection inaccuracy.…”
Section: A Trust-based Protocol For Selfish Nodes Detection In Wmnsmentioning
confidence: 99%